Deactivation of BPJS Healts Coverage and Violations of Workers’ Rights in Industrial Relations Disputes in Indonesia - Amanda Septiani; Jazima Afiq Dayana Chan Lase; Marchellina Rovellie; Anisa Reinata (Media Hukum Indonesia (MHI), 2026)
The deactivation of BPJS Health coverage in industrial relations disputes raises legal issues concerning the fulfillment of workers’ right to social security. In practuce, BPJS Health membership is often linked to employment status, resulting in workers losing access to healthcare service when employment is terminated or disputes arise. This condition reflects a gap between the principle of legal protection for workers and the implementation of the social security system. This study aims to examine the legal protection of workers against the deactivation of BPJS Health and to assess its effectiveness within the Indonesian labor law framework. The research applies a normative juridical method with statutory and case approaches, particularly focusing on the case involving workers of PT Freeport Indonesia. The findings indicate that the deactivation of BPJS Health in industrial disputes potentially undermines workers’ normative rights, especially the right to social security. In addition, the administrative mechanism, which depends on employment status, along with weak supervision, has led to suboptimal legal protection for workers.